Annotated bibliography on agriculture, food, rural development, and environment in Ethiopia - Alemu, Abebaw Getachew (International Food Policy Research Institute, 2002)
This bibliography presents brief results of completed researches, scientific notes and short papers on food, agriculture, rural development, and environment in Ethiopia. It includes materials, the majority of which were published in the 1990s, that are available in different governmental and nongovernmental organizations found in Addis Ababa only. It is believed that the bibliography will help to understand the extent of work done on food, agriculture, water resources, and environment and consequently avoid duplication of work resulting in unnecessary wastage of resources. It also gives a general overview of food security, agriculture, and environmental situation of the country. The publications/documents included in this bibliography, numbering 356 titles, are divided in to four sections: Agriculture [Serial Numbers 1-204]; Food and Nutrition [Serial Numbers 205-280]; Water Resources, Energy, and Irrigation [Serial numbers 281-296]; and Environment [Serial Numbers 297-356]. As is customary with Ethiopian names, the alphabetical order is under the first names. The numbers indicated as superscripts corresponding to the material that they refer to, indicate the location(s) where the particular publication/document is found.